login
a(n) = (n-1)*(a(n-1)+a(n-2)+a(n-3)).
0

%I #4 Oct 26 2019 11:00:07

%S 0,1,1,6,32,195,1398,11375,103744,1048653,11637720,140691287,

%T 1840531920,25907192051,390437813612,6272783063745,107026049110528,

%U 1932717589794045,36828295595429724,738492745452351643

%N a(n) = (n-1)*(a(n-1)+a(n-2)+a(n-3)).

%C Derangement-type sequence like A000166 on the tribonacci A000213.

%t F[1] = 0; F[2] = 1; F[3] = 1; F[n__] := F[n] = (n - 1)*(F[n - 1] + F[n - 2] + F[n - 3]) a = Table[F[n], {n, 1, 25}]

%t RecurrenceTable[{a[1]==0,a[2]==a[3]==1,a[n]==(n-1)(a[n-1]+a[n-2]+a[n-3])}, a,{n,20}] (* _Harvey P. Dale_, Oct 26 2019 *)

%Y Cf. A000166, A000213.

%K nonn

%O 1,4

%A _Roger L. Bagula_, Jun 14 2005